Fetal hemoglobin in umbilical cord blood in preeclamptic and normotensive pregnancies: A cross-sectional comparative study. - Zahra Masoumi; Mary Familari; Karin Källén; Jonas Ranstam; Per Olofsson; Stefan R Hansson (PLoS ONE)
Preeclampsia (PE) is associated with increased fetal hemoglobin (HbF) in the maternal circulation but its source is unknown. To investigate whether excessive HbF is produced in the placenta or the fetus, the concentration of HbF (cHbF) in the arterial and venous umbilical cord blood (UCB) was compared in 15825 normotensive and 444 PE pregnancies. The effect of fetal gender on cHbF was also evaluated in both groups. Arterial and venous UCB sampled immediately after birth at 36-42 weeks of gestation were analyzed for total Hb concentration (ctHb) (g/L) and HbF% using a Radiometer blood gas analyzer. Non-parametric tests were used for statistical comparison and P values < 0.05 were considered significant. Our results indicated higher cHbF in venous compared to arterial UCB in both normotensive (118.90 vs 117.30) and PE (126.75 vs 120.12) groups. In PE compared to normotensive pregnancies, a significant increase was observed in arterial and venous ctHb (171.00 vs 166.00 and 168.00 vs 163.00, respectively) while cHbF was only significantly increased in venous UCB (126.75 vs 118.90). The pattern was similar in both genders. These results indicate a substantial placental contribution to HbF levels in UCB, which increases in PE and is independent of fetal gender, suggesting the elevated cHbF evident in PE results from placental dysfunction.